Psycho‐oncology assessment in Chinese populations: a systematic review of quality of life and psychosocial measures. (20th August 2015) - Hyde, M.K.; Chambers, S.K.; Shum, D.; Ip, D.; Dunn, J.
Abstract : This systematic review describes psychosocial and quality of life (QOL) measures used in psycho‐oncology research with cancer patients and caregivers in China. Medline and PsycINFO databases were searched (1980–2014). Studies reviewed met the following criteria: English language; peer‐reviewed; sampled Chinese cancer patients/caregivers; developed, validated or assessed psychometric properties of psychosocial or QOL outcome measures; and reported validation data. The review examined characteristics of measures and participants, translation and cultural adaptation processes and psychometric properties of the measures. Ninety five studies met review criteria. Common characteristics of studies reviewed were they: assessed primarily QOL measures, sampled patients with breast, colorectal, or head and neck cancer, and validated existing measures (>80%) originating in North America or Europe. Few studies reported difficulties translating measures. Regarding psychometric properties of the measures >50% of studies reported subscale reliabilities < α  = 0.70, <50% reported test–retest reliability, and <30% reported divergent validity. Few reported sensitivity, specificity or responsiveness. Improved accuracy and transparency of reporting for translation, cultural adaptation and psychometric testing of psychosocial measures is needed. Developing support structures for translating and validating psychosocial measures would enable this and ensure Chinese psycho‐oncology clinical practice and research keeps pace with international focus on patient reported outcome measures and data management.